The Correlation of Body Anthropometry and Volleyball Movement Skills - Gilang Nuari Panggraita; Mega Widya Putri; Idah Tresnowati (Universitas PGRI Palembang, 2023)
The purpose of this study was to determine the relationship between body anthropometry and mastery of volleyball movement skills for students at SMA Negeri 1 Kajen. This type of research is Explanatory Research using survey methods. The independent variable is body anthropometry and the dependent variable is volleyball movement skills. The subjects of this study were students of SMA Negeri 1 Kajen who actively participated in volleyball extracurricular activities. The research sample was selected using total sampling technique. The number of samples in this study were 24 subjects. The data collection technique used body anthropometric tests, namely: height, weight, arm length, and leg length as well as volleyball movement skill tests using the American Association for Health, Physical Education Recreation and Dance test guidelines for ages 10-18 years, namely volleyball, service, passing, and set-up tests. Data were analyzed using multiple correlation tests and canonical correlation tests. The results showed that all components of body anthropometry were positively correlated with each component of volleyball movement skills, there was a close relationship between height, arm length and leg length with volleyball, service and set up skills. There is no correlation between all components of body anthropometry and all components of volleyball movement skills together. The conclusion of this study is that the anthropometric components of the body are not correlated with the components of volleyball movement skills together